HUBUNGAN GAYA HIDUP IMPLEMENTASI PERILAKU CERDIK DENGAN KEJADIAN HIPERTENSI PADA USIA DEWASA - Siti Alifia Sawitri; Ditte Ayu Suntara; Siska Pratiwi (Ensiklopedia of Journal, 2026)
Abstract: Hypertension affects approximately 1.3 billion people worldwide. In Indonesia, hypertension ranks third among non-communicable diseases, with approximately 650 million cases, and is a major cause of morbidity and mortality. In Batam City, the number of individuals suffering from hypertension reaches 243,226. Hypertension is caused by several modifiable risk factors, one of which is lifestyle, particularly the implementation of CERDIK health behavior. This study aimed to determine the relationship between lifestyle and the implementation of CERDIK behavior and the incidence of hypertension among adult patients in Buliang Subdistrict, the working area of UPT Batu Aji Public Health Center, Batam City, in 2024.  This study employed a case–control design. The sample consisted of 67 cases and 67 controls. The sampling technique used was non-probability sampling with a purposive sampling method. The results of the Chi-square test showed a p-value of 0.009 with an odds ratio (OR) of 2.654, indicating that H₀ was rejected and Hₐ was accepted. Thus, it can be concluded that there is a significant relationship between lifestyle and the implementation of CERDIK behavior and the incidence of hypertension among adults in Buliang Subdistrict, the working area of UPT Batu Aji Public Health Center, Batam City, in 2024. The OR value of 2.654 indicates that individuals in the control group (non-hypertensive) with poor implementation of CERDIK lifestyle behavior have a 2.654 times higher risk of developing hypertension.  The findings of this study can serve as valuable information for healthcare workers to provide education on the management of non-communicable diseases, particularly hypertension, to all individuals accessing healthcare facilities, encouraging the adoption of healthy lifestyles as modifiable risk factors for hypertension.  Keywords: Hypertension; Adult age; Lifestyle; CERDIK behavior.